Ekonomi Islam Masa Depan - Paturohman, Paturohman (Ecobankers : Journal of Economy and Banking, 2020)
This article discusses the future of Islamic economics, because the capitalist economy which was pioneered by western society and America as the controlling center of capitalist economy has experienced the verge of bankruptcy. Therefore, Islamic economics is a very humane economic science that takes into account the values of the faith and piety. Also Islamic economics is an economic system that does not practice a Ribawi-based financial system but instead promotes interest-free and profit sharing. In this article, the author uses a literature review in his writing. The results of the library research, the authors found an Islamic economic principles based on faith, piety, justice, continuity (istiqomah), compassion (rahmah) and brotherhood. So that the Islamic economy is divided into several parts or designations namely the divine economy, moral economy, humanitarian economics and the middle economy. Keywords: economy; islam; future Abstrak Artikel ini membahas tentang ekonomi Islam masa depan, sebab ekonomi kapitalis yang dipelopori oleh masyarakat barat dan Amerika sebagai pusat pengendali ekonomi kapitalis sudah mengalami diambang kebangkrutan. Oleh sebab itu, ekonomi Islam adalah sebuah ilmu pengetahuan ekonomi yang sangat manusiawi dan memperhatikan nilai-nilai keimanan dan ketakwaan.Juga ekonomi Islam merupakan sebuah sistem ekonomi yang tidak mempraktekkan system keuangan yang berbasis ribawi tetapi lebih mengedepankan bebas bunga dan bagi hasil.Dalam artikel ini, penulis menggunakan kajian pustaka dalam penulisannya.Hasil penelitian pustaka itu, penulis menemukan suatu prinsip-prinsip ekonomi Islam yang berbasiskan keimanan, ketakwaan, keadilan, kesinambungan (istiqomah), kasih sayang (rahmah) dan persaudaraan.Sehingga ekonomi Islam itu terbagi menjadi beberapa bagian atau sebutan yakni ekonomi ilahiayah, ekonomi akhlakiyah, ekonomi kemanusiaan dan ekonomi pertengahan. Kata Kunci: ekonomi; islam; masa depan